A comprehensive study and performance analysis of deep neural network-based approaches in wind time-series forecasting - Rahman M.M.; Shakeri M.; Khatun F.; Tiong S.K.; Alkahtani A.A.; Samsudin N.A.; Amin N.; Pasupuleti J.; Hasan M.K. (Springer Science and Business Media Deutschland GmbH, 2023)
Curve fitting; Deep neural networks; Errors; Forecasting; Gas emissions; Gas plants; Global warming; Graphic methods; Mean square error; Recurrent neural networks; Time series; Time series analysis; Wind; Forecasting: applications; NARX neural network; Network-based approach; Neural network model; Performance; Prediction modelling; Renewable energies; Time series forecasting; Wind speed prediction; Wind time series; Greenhouse gases